Upaya Meningkatkan Hasil Belajar IPA Dengan Menggunakan Model Pembelajaran Reflektif - Zainuddin Zainuddin (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This study aims to improve learning outcomes by using reflective learning models on science subjects of energy materials and changes in class VI SD Negeri 014660 Perk. Padang Pulau academic year 2017/2018. The subjects of this study are all students of class VI which amounted to 16. While the object of this research is the result of student learning on science subjects of energy matter and its changes with the application of learning model reklektif. The data collection tool uses observation and test. In the early pretest obtained the test results of student learning on energy materials and changes yatu with average value 45 and percentage of classical mastery 18.75% (3 students). After applied the reflective learning model in cycle I obtained the achievement level of student achievement reaches the average value 64,37 with the percentage 43,75% (7 students). While in cycle II obtained achievement level of learning achievement reaching average value 82,5 with student mastery percentage equal to 87,5% (14 student). Thus it can be concluded that by using Reflective learning model on the learning process can improve student learning outcomes when applied to science lessons with the material Energy and its changes in Class VI SD Negeri 014660 Perk. Padang Pulau academic year 2017/2018. Keywords: reflective, energy, energy changes Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar dengan menggunakan model pembelajaran reflektif pada mata pelajaran IPA materi energi dan perubahannya di kelas VI SD Negeri 014660 Perk. Padang Pulau tahun pelajaran 2017/2018. Subjek penelitian ini adalah seluruh siswa kelas VI yang berjumlah 16. Sedangkan objek penelitan ini adalah hasil belajar siswa pada mata pelajaran IPA materi energi dan perubahannya dengan penerapan model pembelajaran reklektif. Alat pengumpulan data menggunakan observasi dan tes. Pada pretest awal diperoleh tes hasil belajar siswa pada materi energi dan perubahannya yatu dengan nilai rata-rata 45 dan presentase ketuntasan klasikal 18,75% (3 siswa). Setelah diterapkan model pembelajaran reflektif pada siklus I diperoleh tingkat pencapaian hasil belajar siswa mencapai nilai rata-rata 64,37 dengan presentase 43,75% (7 siswa). Sedangkan pada siklus II diperoleh tingkat pencapaian hasil belajar mencapai nilai rata-rata 82,5 dengan presentase ketuntasan siswa sebesar 87,5% (14 siswa). Dengan demikian dapat disimpulkan bahwa dengan menggunakan model pembelajaran Reflektif pada proses pembelajaran dapat meningkatkan hasil belajar siswa bila diterapkan pada pelajaran IPA dengan materi Energi dan Perubahannya di Kelas VI SD Negeri 014660 Perk. Padang Pulau Tahun Pelajaran 2017/2018. Kata kunci: reflektif, energi, perubahan energi